Pubertal maturation and health risk behaviors in adolescents: a systematic review - Kesley Pablo Morais de Azevedo; Isis Kelly dos Santos; Paulo Moreira Silva Dantas; Maria Irany Knackfuss; Teresa Bento; José Carlos de Leitão; Humberto Jefferson de Medeiros (Epidemiology, Biostatistics and Public Health)
Objective: The objective of this academic work is to demonstrate evidences available in literature about the association among the pubertal maturation and health risk behavior in adolescents.